Perfil imunológico de pacientes com coccidioidomicose crôni- ca e pós-cura e novos reagentes imunobiológicos aplicados ao diagnóstico da doença - Capparelli, Fausto Emíllio (2011)
CHAPTER I - Coccidioidomycosis, known as Valley Fever , is a disease caused by the fungus C. immitis/ C. posadasii. This disease is endemic to the Southwestern United States. Due to the complexity of the disease, multiple tests, such as serological, microbiological and microscopical, should be performed to identify this mycosis. Because of that we have proposed a new approach for the development of novel biomarkers, which is based on the subtractive proteomic strategy known as Phage Display to identify ligands that mimics antigenic mimotopes. Interestingly, the same strategy was used to select antibody fragments, such as scFv (single chain fragment variable) molecules, which may be used to block or neutralize a microorganism, reinforcing its potential use as therapeutic molecules. We showed that one of our selected scFv, clone B8, had high specificity and sensitivity with significant difference between chronic and healthy non-immune patients. Several clones from the peptide biopanning were able to significantly distinguish between purified IgG from chronic patients and healthy non-immune individuals. This investigation brought important perspectives for the diagnosis and therapeutics of the disease. CHAPTER II - Coccidioidomycosis is caused by the pathogenic dimorphic soil-dwelling fungus of the genus Coccidioides. The lack of a thorough understanding of its immune response guided us to investigate the antigen presenting cells profile, and we have successfully demonstrated that specific cell lineages (CD3-CD19- CD14+/-CD11c+/-) present differential expression of receptors and cytokine production. Under stimulation of endospores and spherules, healthy-immune patients presented higher levels of IL-10, and were similar to the chronic patients. We have also observed a significant reduction of PRRs surface expression in CD14+CD11c- cells, such as TLR2, CD206 (Mannose Receptor) and Dectin-1. TLR2 expression from HLA-DR+CD14-CD11c+, HLA-DR+CD14+ and CD14+CD11c+ cells of chronic patients were significantly decreased under same stimuli, which maybe is related with internalization of the receptor after phagocytosis of the fungus.